MARIA BOLKONSKAYA IN THE SYSTEM OF FEMALE IMAGES OF THE NOVEL "WAR AND PEACE" - A.K. Rashidov (Western European Studies, 2024)
Thearticleexamines the image of oneof the keyfemalecharacters of MaryaBolkonskaya. Using herexample, the essence of the concept of "altruism" is revealed,whichhelps to consider the concept of conciliarityin the culturalandreligioustradition of the Russianpeople more deeply
Keywords: concept; Christian tradition; culturalandreligioustradition